2018
DOI: 10.1111/imb.12515
|View full text |Cite
|
Sign up to set email alerts
|

The functions of caspase in whitefly Bemisia tabaci apoptosis in response to ultraviolet irradiation

Abstract: Whiteflies (Bemisia tabaci) are phloem feeders, and some invasive species are composed of cryptic species complexes that cause extensive crop damage, particularly via the direct transmission of plant viruses. Apoptosis is a type of programmed cell death essential for organismal development and tissue homeostasis. The caspases belong to a family of cysteine proteases that play a central role in the initiation of apoptosis in many organisms. Here, we employed a comprehensive genomics approach to identity caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…( Bredesen et al, 2006 ; Fan et al, 2017 ; Jellinger, 2001 ). Only two caspase genes have been characterized in the genome of whitefly, namely, BtCaspase1 and BtCaspase3b , which were demonstrated to be involved in cell death to initiate apoptotic response to UV stress ( Wang et al, 2018 ). Acquiring virions from tomato plants and tobacco plants, and artificial diet, respectively, upregulated the gene transcripts of BtCaspase1 and BtCaspase3b , both in the whole body and head of whitefly ( Figure 2C–D , Figure 2—figure supplement 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( Bredesen et al, 2006 ; Fan et al, 2017 ; Jellinger, 2001 ). Only two caspase genes have been characterized in the genome of whitefly, namely, BtCaspase1 and BtCaspase3b , which were demonstrated to be involved in cell death to initiate apoptotic response to UV stress ( Wang et al, 2018 ). Acquiring virions from tomato plants and tobacco plants, and artificial diet, respectively, upregulated the gene transcripts of BtCaspase1 and BtCaspase3b , both in the whole body and head of whitefly ( Figure 2C–D , Figure 2—figure supplement 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to mammals, caspase-dependent CNS cell death is also responsible for TYLCV-induced neurodegeneration ( Wang et al, 2018 ). For virus-vector interactions, apoptosis is an effective weapon of the innate immunity to eliminate the virus infection, replication, and dissemination within the insect vector ( Chen and Wei, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the caspases can be achieved by activating the mitogen-activated protein kinase (MAPK) pathway which includes the ERK, JNK and p38 families. 4 Stimulation of the MAPK pathway, and so phosphorylation, can affect the expression of transcription factors such as Bcl-2 and p53, and activate the caspase family, leading to the initiation of apoptosis. 5 As reported, the thioredoxin (Trx)/thioredoxin reductase (TrxR) system is highly expressed in many primary tumors, such as hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] UV irradiation is used to activate the DNA damage pathway. The caspase-1 was transcriptionally upregulated in Bemisia tabaci, 43 but post-transcriptionally in S. littoralis in response to UV irradiation. 34 Our result showed that Bdcp-1 was transcriptionally upregulated upon UV irradiation, suggesting that Bdcp-1 was involved in the apoptotic stimuli induced by UV irradiation.…”
Section: Discussionmentioning
confidence: 97%